PROSTITUSI ONLINE DAN EKSISTENSI KEKUASAAN PEMERINTAH - Teza Yudha; Wahyu Utamidewi; Sopyan Resmana Adiarsa (Fakultas Ilmu Sosial and Ilmu Politik Universitas Jenderal Soedirman, 2018)
Information globalization has placed Indonesia as part of the world's information society, requiring the establishment of arrangements for the management of information and electronic transactions at the national level. In line with these developments, the internet has changed everything, from the way people think, communicate, connect, work, shop, to the pattern of people in making love. Sexual access can now be easily obtained, from contemporary pornographic content to online prostitution, produced and distributed massively and very quickly on the internet.The idea of sexuality that used to be taboo now obtains a space to discuss. Through the internet, sexuality is used as a recreational arena and a biological necessity as an essential outlet for desire and lust. As Foucault shows that sexuality is not merely a biological drive, but is a form of behavior and thoughts that are subordinated by power relations that are carried out for the purpose other objectives outside the interests of sexuality itself. It is this power that should be used as